Implementasi Model Pembelajaran Project Based Learning (PjBL) Dalam Menumbuhkan Kreativitas Siswa - Dhamas Mega Amarlita; Endang Utaminingsih (Journal on Education, 2024)
Creativity in science, technology and various aspects of daily life needs to be developed to be able to compete in the development of superior human resources. Therefore, in education, especially in learning, the use of appropriate learning methods to hone students' creativity and critical thinking skills. One method that can answer this challenge is the project-based learning (PjBL) model. This study aims to determine the implementation of the PjBL learning model in fostering student creativity, especially in creating products on electrochemical material. Which was carried out on class X students at SMK Islam 1 Blitar. Based on the results of the study, it is concluded that PjBl is an effective method to foster student creativity. By giving students the freedom to identify and solve problems, collaborate with teams and think creatively, it can motivate students to produce innovative and creative ideas that can be seen from the products produced.